Simple systemic index associated with oxaliplatin‐induced liver damage can be a novel biomarker to predict prognosis after resection of colorectal liver metastasis. Issue 6 (25th May 2022) - Shimagaki, Tomonari; Sugimachi, Keishi; Mano, Yohei; Onishi, Emi; Iguchi, Tomohiro; Uehara, Hideo; Sugiyama, Masahiko; Yamamoto, Manabu; Morita, Masaru; Toh, Yasushi
Abstract: Aim: Oxaliplatin, an anticancer drug for advanced colorectal cancer, causes liver sinusoidal damage, sometimes with portal hypertension. We conducted a retrospective comparative study of the relationship of liver sinusoidal disorders and liver function with the prognosis in patients who underwent hepatectomy for colorectal liver metastasis (CRLM). Methods: In total, 158 patients who underwent hepatectomy for CRLM were included in the study, and the effect of chemotherapy‐associated liver damage on the prognosis was examined. Results: Preoperative oxaliplatin was used in 75 of 158 patients; of these 75 patients, 26 had intraoperative blue liver (BL). In a comparison of the BL group (n = 26) and non‐BL group (n = 132), patients in the BL group had a significantly lower serum albumin concentration and a significantly higher indocyanine green test result, aspartate aminotransferase‐to‐platelet ratio index (APRI), and FIB‐4 score. Operative morbidities were not significantly different between the two groups. The overall survival rate after hepatectomy was significantly worse in the BL group than in the non‐BL group. In the univariate analysis, the serum albumin concentration, indocyanine green test, a high tumor burden score (TBS), and the APRI were statistically significant poor prognostic factors. In the multivariate analysis, the APRI and a high TBS were independent poor prognostic factors. Conclusion: The APRI and TBS in patients with CRLM are prognostic predictors after hepatectomy for metastatic liver cancer. This study indicated that liver damage in patients treated with preoperative oxaliplatin has an effect on the prognosis. Abstract : APRI and TBS as OS‐independent factors in patients who underwent hepatectomy for colorectal liver metastasis.